TAK-875 Reduces HbA1C in Patients with T2DM - Vinall, Maria (MD Conference Express, 2011)
TAK-875 is a selective G-protein-coupled receptor 40 (GPR40) agonist that is being developed as an adjunct therapy to diet and exercise to improve glycemic control in patients with type 2 diabetes mellitus. Results of a Phase 2 [NCT01007097] trial that has shown the glucose-lowering efficacy, safety, and tolerability of TAK-875 in a clinical setting are discussed.